Nerve allografts supplemented with schwann cells overexpressing glial‐cell‐line–derived neurotrophic factor. Issue 2 (21st November 2012) - Santosa, Katherine B.; Jesuraj, Nithya J.; Viader, Andreu; MacEwan, Matthew; Newton, Piyaraj; Hunter, Daniel A.; Mackinnon, Susan E.; Johnson, Philip J.
Abstract Introduction: We sought to determine whether supplementation of acellular nerve allografts (ANAs) with Schwann cells overexpressing GDNF (G‐SCs) would enhance functional recovery after peripheral nerve injury. Methods: SCs expanded in vitro were infected with a lentiviral vector to induce GDNF overexpression. Wild‐type SCs (WT‐SCs) and G‐SCs were seeded into ANAs used to repair a 14‐mm nerve gap defect. Animals were harvested after 6 and 12 weeks for histomorphometric and muscle force analysis. Results: At 6 weeks, histomorphometry revealed that ANAs supplemented with G‐SCs promoted similar regeneration compared with isograft at midgraft. However, G‐SCs failed to promote regeneration into the distal stump. At 12 weeks, ANAs with G‐SCs had lower maximum and specific force production compared with controls. Conclusions: The combined results suggest that consistent overexpression of GDNF by G‐SCs trapped axons in the graft and prevented functional regeneration. Muscle Nerve, 2013